SP6.1.1 Cholecystectomy or expectant management after endoscopic sphincterotomy and bile duct stone removal?. (28th October 2021) - Toogood, Kate; Pike, Thomas; Coe, Peter; Everett, Simon; Toogood, Giles; Smith, Andrew
Abstract: Aims: Following ERCP, NICE guidance suggests that surgically fit patients undergo cholecystectomy to prevent recurrence of choledocholithiasis and its complications. However, for many patients who are deemed unfit or who choose not to have surgery, ERCP is their definitive management. This study examines the clinical outcomes and costs of expectant management (EM) or cholecystectomy following ERCP. Methods: All patients that underwent ERCP, sphincterotomy and common bile duct (CBD) clearance at St James's University Hospital between January 2015 and December 2018 were identified from a prospectively maintained ERCP database. The clinical outcomes for patients that had undergone an ERCP, sphincterotomy and CBD clearance for gallstones were identified from their electronic patient record. A cost analysis for the complete patient pathway was performed. Results: 820 patients underwent ERCP and CBD clearance for gallstones with a median 3.9 year follow up. 222 patients had undergone a cholecystectomy prior to ERCP and were excluded from analysis. 203 patients underwent planned cholecystectomy with 15% (31 patients) requiring complex surgery and 12% (24 patients) needing readmission. 395 patients received expectant management (EM). 9 (2.3%) patients returned with CBD stone symptoms, 6 (1.5%) went on to laparoscopic cholecystectomy (LC). The readmission rate in the EM group was 9%. The average cost per patient in the expectant management group was £7, 487 and in the cholecystectomy group was £10, 584. Conclusion: The results from this study suggest that the need for cholecystectomy following ERCP is uncertain, with similar rates of biliary re-admissions in both groups.